Influence of bone augmentation procedures on the short-term prognosis of simultaneously placed implants - Rammelsberg, Peter; Schmitter, Marc; Gabbert, Olaf; Lorenzo Bermejo, Justo; Eiffler, Constantin; Kappel, Stefanie (Clinical oral implants research, 2012)
Objectives The purpose of this study was to investigate the effect of simultaneous bone-augmentation procedures, and their combination, on the survival of dental implants and on the incidence of complications. Material and methods Within a retrospective analysis, 958 implants placed in 404 patients (mean age 58.18) were selected from a prospective clinical study. In 304 cases of reduced bone width, bone spreading (n = 217) with hand osteotomes, or bone splitting (n = 15), or guided bone regeneration (n = 72) combined with autogenous bone grafts were also performed. Eighty-eight implants were placed in combination with simultaneous internal sinus floor elevation without using graft material. For 194 additional implants, several augmentation procedures were combined because of extensive bone deficits. Three-hundred and seventy-two conventionally placed implants served as controls. Implant failures and complications were recorded after a mean observation period of 2.1 years (maximum 6.9 years). Results Seventeen failures and nine additional implant-related complications were observed. After 4 years, Kaplan-Meier curves revealed a probability of survival without complication of 97.5% for conventionally placed implants, and 95.8% for implants placed in combination with a single augmentation technique. If several augmentation techniques were combined, success decreased to 94.1%. Complication-free survival differences between combined augmentation techniques and conventionally placed implants were significant (P = 0.004). Age, gender, and location showed no effect on implant survival. Conclusions It can be concluded that simultaneous bone-augmentation techniques slightly reduce short-term prognosis for dental implants. This effect was more pronounced when advanced defects required the combination of several augmentation procedures.